63 Chronic Femoral Osteomyelitis Case Series: Outcomes and Economic Impact at A United Kingdom Based Tertiary Centre. (4th May 2021) - Lau, E; Arshad, Z; Aslam, A; Thahir, A; Krkovic, M
Abstract: Introduction: Osteomyelitis refers to an inflammatory process affecting bone and bone marrow. This study reviews chronic femoral osteomyelitis treatment and outcomes, including economic impact. Method: We retrospectively collected data from a consecutive series of 14 chronic femoral osteomyelitis patients treated between January 2013 and January 2020. Data collected include patient demographics, comorbidities, pathogens, complications, treatment protocol and costs. Functional outcome was assessed using EuroQOL five-dimensional interview administration questionnaire (EQ-5D-5L™) and EuroQOL Visual Analogue Scale (EQ-VAS™). Results: Of these, 92.9% had one or more osteomyelitis risk factor, including smoking and diabetes. Samples from 78.6% grew at least one pathogen. Only 42.9% achieved remission after initial treatment, but 85.7% were in remission at final follow-up, with no signs of recurrence throughout the follow-up period (mean: 21.4 months). The average treatment cost was £39, 249.50 with a net mean loss of £19, 080.10 when funding was considered. The mean-derived EQ-5D score was 0.360 and the mean EQ-VAS score was 61.7, lower than their values for United Kingdom's general population, p = 0.0018 and p = 0.013 respectively. Conclusions: Chronic femoral osteomyelitis treatment is difficult, resulting in significant economic burden. With previous studies showing cheaper osteomyelitis treatment at specialist centres, our net financial loss incurred suggests the need for management at specialised centres.